2014
DOI: 10.3917/spub.144.0547
|View full text |Cite
|
Sign up to set email alerts
|

Connaissances, attitudes et pratiques des chefs de ménage de la commune d'Abobo (Abidjan, Côte d'Ivoire) en matière de rage, en 2008

Abstract: This study shows a good level of knowledge of household heads concerning rabies. However, harmful health practices persist. Public awareness of rabies therefore needs to be reinforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Only half of our study population had heard of rabies. This proportion is considerably lower than reported in other sub-Saharan African countries, where 76%–99% of respondents had heard of rabies [37,47,84,85,86,87]. The majority of respondents knew that rabies is primarily transmitted through infected dogs (94%) via bites (88%).…”
Section: Discussionmentioning
confidence: 74%
“…Only half of our study population had heard of rabies. This proportion is considerably lower than reported in other sub-Saharan African countries, where 76%–99% of respondents had heard of rabies [37,47,84,85,86,87]. The majority of respondents knew that rabies is primarily transmitted through infected dogs (94%) via bites (88%).…”
Section: Discussionmentioning
confidence: 74%
“…However, the different post-exposure management protocols were unknown to them. Tiembre and col. in Abidjan had found that vaccination (79.82%) was known as the main means of protection against rabies [17]. In the study by Adje and col, on the other hand, the vaccine as a means of prevention was not known by 39% and 55% of students respectively [14].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies [23][24][25] have explored rabies surveillance in the western region of Cameroon, in line with WHO recommendations highlighting the importance of involving communities and health facilities at all levels of the health system [26]. To this end, the 658 participants involved in this study included 273 health professionals of which 235 were rabies surveillance focal points and 38 were zoo technical station managers, while 385 respondents were community members and victims of dog bites.…”
Section: Discussionmentioning
confidence: 99%